L'omogenitorialità tra autodeterminazione e desiderio di trasparenza. Autobiografie di famiglia - Giuseppe Masullo (Culture e Studi del Sociale)
The article examines some aspects called into question by the debate on same-sex families in Italy. We start from the writings of Giuseppina La Delfa, French language teacher and LGBT activist, who has been fighting for years for the recognition of the rights of “Famiglie Arcobaleno” (Rainbow Families), the name of the association she founded in 2005. The two autobiographical books here reviewed testify to the strong link existing between self-acceptance as homosexuals and the possibility of creating a same-sex family. Transparency and visibility of choices thus become the most effective weapons to address the complex issues posed by a society that still struggles to conceive the family as the result of “conscious” and “co-responsible” choices and the parental skills as independent from gender and sexual orientation.